Flock House Virus RNA Polymerase Is a Transmembrane Protein with Amino-Terminal Sequences Sufficient for Mitochondrial Localization and Membrane Insertion - Miller, David J. (American Society for Microbiology, 2002)
Localization of RNA replication to intracellular membranes is a universal feature of positive-strand RNA viruses. Replication complexes of flock house virus (FHV), the best-studied alphanodavirus, are located on outer mitochondrial membranes in infected Drosophila melanogaster cells and are associated with the formation of membrane-bound spherules, similar to structures found for many other positive-strand RNA viruses. To further study FHV replication complex formation, we investigated the subcellular localization, membrane association, and membrane topology of protein A, the FHV RNA-dependent RNA polymerase, in the yeast Saccharomyces cerevisiae, a host able to support full FHV RNA replication and virion formation. Confocal immunofluorescence revealed that protein A localized to mitochondria in yeast, as in Drosophila cells, and that this mitochondrial localization was independent of viral RNA synthesis. Nycodenz gradient flotation and dissociation assays showed that protein A behaved as an integral membrane protein, a finding consistent with a predicted N-proximal transmembrane domain. Protease digestion and selective permeabilization after differential epitope tagging demonstrated that protein A was inserted into the outer mitochondrial membrane with the N terminus in the inner membrane space or matrix and that the C terminus was exposed to the cytoplasm. Flotation and immunofluorescence studies with deletion mutants indicated that the N-proximal region of protein A was important for both membrane association and mitochondrial localization. Gain-of-function studies with green fluorescent protein fusions demonstrated that the N-terminal 46 amino acids of protein A were sufficient for mitochondrial localization and membrane insertion. We conclude that protein A targets and anchors FHV RNA replication complexes to outer mitochondrial membranes, in part through an N-proximal mitochondrial localization signal and transmembrane domain.